ANZUS and Australia's Security: Australian Attitudes, May 1984 (ADA Dataverse, 2018)
Topics in this survey include: countries threatening Australia's security; importance ANZUS treaty; US or Australia benefits more from ANZUS; visits by warships with nuclear powered engines to Australian ports; trust in US to come to Australia's defence. Standard variables include Federal and State voting intention, household size, age, marital status, schooling, occupation of respondent or of main income earner, household income, country of birth, industry sector, religion, tenure of dwelling, sex, area. This study is part of a series (SSDA No's 525 to 532) commissioned by the United States Information Service between 1982 and 1985 on Australians' attitudes to defence issues. Similar studies were carried out in New Zealand at the same time (SSDA No's 521 to 524) which contain some parallel questions.